The Relationship of Self-Acceptance with Dieting Behavior in Women - Nagoklan Simbolon; Pomarida Simbolon (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Women who have self-acceptance will encourage individuals to accept their body size, reduce weight by dieting and care about physical health, where diet is a person's conscious effort to limit and control the food to be eaten to reduce and maintain weight. The purpose of this study was to determine the relationship between self-acceptance and dietary behavior in women at the Nadin gym in 2021. This research method used an analytical survey research design using a cross-sectional approach. The sample in this study was 40 respondents with the sampling technique being total sampling. The instrument used was a questionnaire and the data were analyzed by a chi-square test. The results of this study obtained self-acceptance in the low category 21 people (52.5%), dietary behavior in the poor category 25 people (62.5%) with the results of the Chi-square statistical test obtained a p-value of 0.001 (p less than 0.05) indicating that there is a relationship between self-acceptance and dietary behavior in women at Nadin Gym in 2021. It is hoped that Nadin Gym women will continue to pay attention to diet so that they can implement appropriate dietary behavior. good for maintaining health. Abstrak: Wanita yang memiliki penerimaan diri akan mendorong individu untuk menerima ukuran tubuhnya, mengurangi berat badan dengan melakukan perilaku diet serta peduli tentang kesehatan fisik, dimana diet merupakan usaha sadar seseorang dalam membatasi dan mengontrol makanan yang akan dimakan dengan tujuan untuk mengurangi dan mempertahankan berat badan. Tujuan penelitian ini adalah untuk mengetahui hubungan penerimaan diri dengan perilaku diet pada wanita di nadin gym tahun 2021. Metode penelitian ini menggunakan rancangan penelitian survey analitik dengan menggunakan pendekatan cross-sectional. Sampel dalam penelitian ini 40 responden dengan teknik pengambilan sampel adalah total sampling. Instrumen yang digunakan adalah kuesioner dan data dianalisis dengan uji chi-square. Hasil dari penelitian ini diperoleh body dissatisfaction pada kategori rendah 21 orang (52.5%), perilaku diet pada kategori tidak baik 25 orang (62,5%) dengan hasil uji statistik chi-square diperoleh nilaip-value 0.001 (p kurang dari 0.05) menunjukkan bahwa adanya hubungan penerimaan diri dengan perilaku diet pada wanita di Nadin Gym tahun 2021. Diharapkan kepada wanita Nadin Gym tetap memperhatikan diet, sehingga dapat menerapkan perilaku diet yang baik untuk tetap menjaga kesehatan.